Effectiveness of Trastuzumab Combined With Capecitabine Treatment in a Patient With Hilar Cholangiocarcinoma Complicated by Liver Metastases With an ERBB2-Activating Mutation: A Case Report - Zeng, Daobing; Zhao, Xiaofei; Di, Liang; Lou, Luyan; Song, Yanfang; Zhang, Yanrui; Liu, Huanhuan; Li, Guangming (Frontiers in Oncology, 2022)
The identification of ERBB2 (HER2) alteration in some solid tumors has become critically important due to the actionable events predictive of response to anti-HER2 therapy. However, the efficacy of ERBB2 mutated hilar cholangiocarcinoma (hCCA) against ERBB2 is rarely reported. Here we report a 76-year-old female diagnosed with hCCA complicated by liver metastases after radical resection. The next-generation sequencing assay showed that the tumor had an ERBB2 mutation. Then, the patient was treated with trastuzumab plus capecitabine. After 2 months of treatment, she had a partial response. Until now, the patient is still alive. This study has shown the potential of trastuzumab combined with capecitabine as an effective treatment for hilar cholangiocarcinoma complicated by liver metastases harboring ERBB2 alterations.